Probability Distribution for Mobilized Shear Strengths of Saturated Undrained Clays Modeled by 2-D Stationary Gaussian Random Field - A 1-D Stochastic Process View. (13th March 2014) - Ching, J.; Lin, C.-J.
ABSTRACT This paper shows that the mobilized shear strength of a two-dimensional (2-D) spatially variable saturated undrained clay is closely related to the extreme value of a one-dimensional (1-D) continuous stationary stochastic process. This 1-D stochastic process is the integration of the 2-D spatially variable shear strength along potential slip curves. Based on this finding, a probability distribution model for the mobilized shear strength of the 2-D clay is developed based on a probability distribution model for the extreme value of the 1-D stochastic process. The latter (the model for the 1-D extreme value) has analytical expressions. With the proposed probability distribution model, the mobilized shear strength of a 2-D clay can be simulated without the costly random field finite element analyses.